RANCANGAN KUALITAS PELAYANAN UNIT BPPT ENJINIRING DENGAN INTEGRASI SERVQUAL, IPA DAN KANO MODEL DALAM MODEL QFD - Muktiyono Muktiyono (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. BPPT as a Non-Government Organization (LPNK) that one work unitbelow it is the Technology Service Center/BPPT Enjiniring as a Public ServiceAgency (BLU) at the Agency for the Assessment and Application of Technology(BPPT) is a form of willingness to perform services or dissemination oftechnology institutional engineering capabilities in delivering goods and services.This study aims to determine the attributes of what services are needed Customersand performance attributes of service quality, to analyze the differences betweenthe perceptions and expectations of the customers on the quality of existingservices (the level of customer satisfaction), and determine the form of planningin improving the quality of service with HoQ (servqual) and HoQ Kano. Thisstudy uses four methods: Servqual, IPA, Kano Model and QFD. After calculationof the obtained data shows that the gap the average score obtained from the 35service attributes is -0.06. There are 5 main technical response that needs to bedone by BPPT Enjiniring management in an effort to improve the quality ofservice is: the work of partner received correctly, proper and lawful, Servicesstraightforward, easy to understand and easy to implement, Implementation of thework can be completed on time have been determined, the Environment mustorderly, organized, provided a comfortable waiting room, clean and tidy, and thedevelopment of consumer claims handling sectionKeywords: Servqual, IPA, Kano Model, QFD, House of Quality, BPPTEnjiniring